(untitled) (Research, Society and Development, 2020)
Odontogenic keratocyst (OKC) is a lesion which origin is the dental epithelium, it has a predilection for presenting itself in the posterior portion of the mandible and is considered one of the most common lesions within odontogenic cysts. The following study presents a case of Odontogenic Keratocyst of a large dimension. A female patient presents with inflammatory symptoms at the level of the jaw. In the intraoral physical examination a palpation test was performed and together with radiographic examinations, in which a multilocular radiolucent image of 8x3 cm was determined. Subsequently, a biopsy was performed and the histology was compatible with Odontogenic Keratocyst. This article reviews the etiopathogenesis, clinical, radiographic, histopathological, immunohistochemical and treatment; with the aim of describing the importance of this lesion due to its ability to reach large dimensions and present high recurrence. Therefore, it is important to make a correct diagnosis that allows to establish an adequate treatment plan for this lesion.